Potential of Trichoderma species on Helminthosporium causing leaf spot on cane palm, Chrysalidocarpus lutescens. - Jegathambigai, V.; Karunaratne, M.D.; Svinningen, A.; Mikunthan, G. (My University, 2008)
The cane palm, Chrysalidocarpus lutescens is one among the plant material of the export industries in Sri Lanka. The export quality of C. lutescens was declined due to the repeated occurrence of a leaf spot caused by Helminthosporium. Widespread occurrence of the leaf spot affected the cane palm production and succumb it to a huge setback in the floriculture industry in Sri Lanka. Being an export industry eco-friendly means of disease control was the prime focus for a better management of such vulnerable disease. Trichoderma is a potential bio agent, which has definite role in suppressing the inoculum of Helminthosporium sp. This study aims to evaluate the efficacy of Trichoderma species to control naturally established leaf spot in cane palm under field conditions. Three isolates of T. viride and two isolates of T. harzianum were evaluated. All the Trichoderma species performed significantly in reducing the disease incidence. T. viride + T. harzianum combination (1 x 10(10) cfu/ml) was the best compared to chemical in decreasing the mean disease severity index and improving the frequency of healthy plants. The colour of the leaves regained due to the application of Trichoderma sp. The results revealed that leaf spot incidence was lowered significantly in cane palms treated with Trichoderma species followed by treatment with combination of Trichoderma sp. and fungicides. The fungicide mixture (hexaconozole 50 g/l + Isoprothiolane 400 g/l) failed to lower the disease incidence and had no effect in suppressing the inocula of Helminthosporium, although recommended. Mixing of Trichoderma species with fungicide did not exhibit any additive effect. The combination of different species of Trichoderma would target species of Helminthosporium that exist as a complex group under field conditions. The results also proved that the existence of heterogeneity in Helminthosporium that could be tackled and effectively controlled by a combination of different species of the bio-agent, if available, to broaden the selectivity of the pathogens. The use of Trichoderma species had claimed not only to reduce the incidence of Helminthosporium but also to sustain the growth and vigor of the C. lutescens to most fit for exporting.